Cross-sectional analysis on publication status and age representation of clinical studies addressing mechanical ventilation and ventilator-induced lung injury in infants and children - Patry, Christian; Kranig, Simon A.; Rafat, Neysan; Schaible, Thomas; Tönshoff, Burkhard; Hoffmann, Georg F.; Ries, Markus (BMJ open, 2018)
Objectives: We determined the number and time-to-public availability of study results of published and unpublished clinical studies in paediatric mechanical ventilation (MV) and ventilator-induced lung injury (VILI), which were registered as completed on ClinicalTrials.gov. Furthermore, we explored the pattern of represented research study subtopics and the corresponding study populations. Setting: Literature search based on ClinicalTrials.gov, PubMed and Google Scholar from 9 July 2017 to 27 September 2017. Primary and secondary outcome measures: Assessment, if studies included in our analysis had been published. Assessment of primary research focus, patient enrolment and age representation of the analysed studies. Results: We identified n=109 registered and completed clinical studies on paediatric MV and VILI (enrolment: 22 233 participants). 71% were published, including data from 18 647 subjects. 29% of studies were unpublished, containing data from 3586 subjects. Median time-to-public availability of study results was 22 (IQR, 12.8-41.5) months. The most important study subtopics were biophysical and technical aspects of MV (32 studies), administration of drugs to mitigate VILI through various mechanisms (40 studies) and diagnostic procedures (16 studies). n=66/109 (61%) studies exclusively focused on children below 1 year of age and n=2/109 (2%) exclusively on children between 1 and 14 years. Conclusions: One-third of clinical studies in paediatric MV and VILI registered as completed on ClinicalTrials.gov remained unpublished and contained data on 3586 study participants. The overall median time-to-public availability of study results was longer than the deadline of 12 months mandated by the Food and Drug Administration Amendment Act of 2007. Important and clinically relevant research study subtopics were represented in the research questions investigated in paediatric MV and VILI. The study population was skewed towards children younger than 1 year which indicates, that there is a substantial need for clinical VILI research in older children.